Basal cell carcinoma of the prostate: a case report of a rare prostate cancer and review of the literature - Puglisi, Silvia; Cremante, Malvina; Rescigno, Pasquale; Gandini, Annalice; Zanardi, Elisa; Fornarini, Giuseppe; Rebuzzi, Sara Elena (Acta Biomedica Atenei Parmensis, 2023)
Basal cell carcinoma (BCC) of the prostate is a very rare histologic variant of prostate cancer, of difficult diagnosis and uncertain prognosis. In fact, despite the frequency of prostate cancer, only 100 cases have been described in the literature, and most of the data derived from case reports. Because of the rarity of this disease, therapeutic options for these patients are scarce and no randomized trials are available. Here, we report the case of a 63-year-old man treated for a prostatic BCC (pBCC) that was challenging in terms of both diagnosis and treatment. We also performed a review of the literature to provide an overview of the therapeutic options for this rare tumor type and to better understand the role of molecular characterization in rare prostate cancer histologies. Given the rarity of pBCC worldwide, further collection of real-world data is needed to better understand the optimal diagnostic and therapeutic strategies for this rare disease.